Assessment of Seismic Risk in Istanbul - Seda Kundak; Turkoglu Handan (European Regional Science Association (ERSA), 2005)
The 1999 earthquakes occurred in Turkey caused destructions in every field and level in nation wide with the high number of deaths and injuries, the remarkable rates of collapsed and heavily damaged buildings and the interruption of business activities in long-term. In the last 5 year-period, various scientific researches focusing on seismic issues have investigated the relationships among seismicity, site conditions and vulnerability. Moreover, with the co-operations of central and local governments, universities and international agencies, many comprehensive projects have been carried out, such as "A Disaster Prevention/Mitigation Basic Plan for Istanbul” by Istanbul Greater Municipality - Japan International Cooperation Agency. Despite 1999 earthquakes had slight effects on Istanbul, the probability of a great earthquake (estimated to occur up to 30 years), has accelerated the attempts on risk evaluation, development of mitigation strategies, readjustment of disaster management system and so on. The primary studies on this field are focused on understanding seismicity and site conditions at large scale so that the earthquake maps produced show risky zones related to geological indicators. Aftermath of many great disasters, it has been observed that land-use decisions, demographic and economic pattern are the key components which increase or decrease the vulnerability level of settlements. In this context, the aim of this paper is to evaluate vulnerability components affecting risk levels and to explore risky zones of Istanbul. In this paper, urban and seismic indicators (i.e. site conditions, demography, land use, economy) have been aggregated and factor analysis has been used in order to reveal principal components of earthquake risk in Istanbul. According to these main factors, using cluster analysis, the critical zones of Istanbul have been indicated on urban pattern.
Keywords: 330